Physical therapy evaluation and treatment in distal radius fracture: a case report - Graciosa, Maylli Daiani; Martins, Tamiris Beppler; Santos, Keyla Mara dos; Palandi, Juliete; Sinhorim, Larissa; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: subjects who have suffered DRF submitted immobilization may have a loss in active range of motion and functional deficit. Objectives: evaluate changes in the wrist and verify the effectiveness of physical therapy intervention used in the treatment of DRF. Methods: a physiotherapy evaluation form, goniometry and Visual Analogue Scale were used to assess the patient. A treatment protocol was applied for seven sessions. Results: the results showed reduced pain and increased range of motion of the wrist. Conclusion: there were changes as pain and reduced range of motion of the wrist. The treatment protocol was effective for these changes.